Proceedings International Conference on Dependable Systems and Networks
DOI: 10.1109/dsn.2002.1028916
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a COTS system for space applications

Abstract: This paper evaluates the impact of transient errors in the operating system of a COTS-based system (CETIA board with two PowerPC 750 processors running LynxOS) and quantifies their effects at both the OS and at the application level. The study has been conducted using a Software-Implemented Fault Injection tool (Xception) and both realistic programs and synthetic workloads (to focus on specific OS features) have been used. The results provide a comprehensive picture of the impact of faults on LynxOS key featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 7 publications
2
14
0
1
Order By: Relevance
“…Most faults injected into the system either had no effect or caused a process to crash. This result is consistent with fault injection experiments performed on other systems (Madeira et al, 2002).…”
Section: Fault Tolerance Validation Using Fault Injectionsupporting
confidence: 82%
See 1 more Smart Citation
“…Most faults injected into the system either had no effect or caused a process to crash. This result is consistent with fault injection experiments performed on other systems (Madeira et al, 2002).…”
Section: Fault Tolerance Validation Using Fault Injectionsupporting
confidence: 82%
“…Fault injection experiments on other systems (Madeira et al, 2002) have shown that most transient hardware faults either have no effect, cause a process to crash, or cause the entire node to crash. In practice faults are infrequent.…”
Section: Assumptionsmentioning
confidence: 99%
“…Madeira et al [26] focused on physically induced errors to evaluate the use of COTS systems for space applications. Randomly distributed faults have been injected into both registers and memory of a system running LynxOS, a POSIX conform RTOS.…”
Section: Related Workmentioning
confidence: 99%
“…nineties, Kao et al [26] injected memory faults into the kernel address space of a UNIX operating system. Fabre et al [27] performed similar fault-injection experiments with a microkernel operating system, and so did Madeira et al [28] with a UNIX-like real-time operating system. More recently, the Linux kernel has been analyzed [29], [30].…”
Section: A Susceptibility Analyses Of Operating Systems To Memory Ermentioning
confidence: 95%